Utility Evaluation of Porcine Enteroids as PDCoV Infection Model in vitro - Luo, Hao; Zheng, Jingyou; Chen, Yunlu; Wang, Tingjun; Zhang, Zhenning; Shan, Ying; Xu, Jidong; Yue, Min; Fang, Weihuan; Li, Xiaoliang (Frontiers in Microbiology, 2020)
Porcine deltacoronavirus (PDCoV) is a novel emerging enteric coronavirus found in pigs. Intestinal enteroids, which partially recreate the structure and function of intestinal villi-crypts, have many physiological similarities to the intestinal tissues in vivo. Enteroids exhibit advantages in studying the interactions between intestines and enteric pathogens. To create a novel infection model for PDCoV, we developed an in vitro system to generate porcine intestinal enteroids from crypts of duodenum, jejunum, and ileum of pigs. Enterocytes, enteroendocrine cells, Paneth cells, stem cells, proliferating cells, and goblet cells were found in the differentiated enteroids. Replication of PDCoV was detected in the cultured enteroids by immunofluorescence and quantitative RT-PCR. Double immunofluorescence labeling demonstrated that PDCoV was present in Sox9-positive intestinal cells and Villin1-positive enterocytes. There were multiple cellular responses shown as changes of transcription of genes related to mucosal immunity, antiviral genes, and marker genes of stem cells and other cells in the enteroids infected with PDCoV. We conclude that the 2-D enteroids derived from porcine jejunum can be used as an in vitro multicellular model for the investigation of pathogenesis and host immune responses to porcine enteric pathogens, such as PDCoV.